Evaluación del proceso de biodegradación de residuos orgánicos domésticos utilizando Hermetia Illucens en la ciudad de Bogotá (2022)
The main objective of this research is the evaluation of a biodegradation process of domestic organic waste with the help of the living organism known as Hermetia Illucens or Black Soldier Fly (BSF); decomposer beings that present high efficiencies, potential to be agents of degradation of plant material or garbage that is considered "unusable" for many, but beneficial for others. This evaluation is carried out taking into account operating variables such as temperature, humidity, feeding rate and, on the other hand, control variables such as pH, humidity/temperature of the substrate and larval growth.